2003
DOI: 10.1097/01.mp.0000071842.83169.5a
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Glutathione S-Transferase-Pi in Invasive Breast Cancer

Abstract: Glutathione S-transferase pi (GST-pi), a Phase II detoxification enzyme, has recently been implicated in protection against apoptosis. Expression of GST-pi and Bcl-2 protein, an established apoptosis marker, was analyzed by immunohistochemistry in 116 cases of infiltrative ductal breast carcinomas in Singapore women. The markers were correlated with apoptosis detected by the TUNEL method and clinico-pathological parameters. There were 67 (58%) GST-pi-positive breast tumors and 43 (37%) Bcl-2-positive tumors. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 31 publications
5
59
1
3
Order By: Relevance
“…5,6 However, this invaluable function is disadvantageous during chemotherapy, when enhanced detoxification by the glutathione/GST pathway may result in tumor resistance to cytotoxic agents. 20 Previous in vitro investigations and clinical studies have demonstrated that high levels of GST enzymes in tumors are associated with weaker responses to chemotherapy and poorer survival in patients with carcinomas of the breast, 21 stomach, 22 esophagus, 23 ovary, 24,25 and head and neck. 26 To our knowledge, only two studies on GSTP1 polymorphisms and breast carcinoma survival, conducted in the United States 14 and the United Kingdom, 15 respectively, have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, this invaluable function is disadvantageous during chemotherapy, when enhanced detoxification by the glutathione/GST pathway may result in tumor resistance to cytotoxic agents. 20 Previous in vitro investigations and clinical studies have demonstrated that high levels of GST enzymes in tumors are associated with weaker responses to chemotherapy and poorer survival in patients with carcinomas of the breast, 21 stomach, 22 esophagus, 23 ovary, 24,25 and head and neck. 26 To our knowledge, only two studies on GSTP1 polymorphisms and breast carcinoma survival, conducted in the United States 14 and the United Kingdom, 15 respectively, have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…In neoplasms other than lung cancer, the overexpression of GST-pi and P-gp has been associated with decreased treatment response and survival. [16][17][18] In patients with lung cancer, the link between GST-pi and P-gp expression and tumor chemosensitivity has been documented by several trials in advanced NSCLC. 4,5,[7][8][9][10][11] In this regard, Hida et al observed that pretreatment serum GST-pi levels may be a useful parameter for predicting therapeutic response to combination chemotherapy regimens that include platinum compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date the results are still somewhat controversial and may vary from population to population. (Gilbert et al, 1993;Silvestrini et al, 1997;Buser et al, 1997;Helzlsouer et al, 1998;Millikan et al, 2000;Mitrunen et al, 2001;Gudmundsdottir et al, 2001;Huang et al, 2003;Egan et al, 2004;Sreenath et al, 2005;Moureau-Zabotto et al, 2006;Unlu et al, 2008;Saxena et al, 2009;Arun et al, 2010;Pongtheerat et al, 2011;Zhang et al, 2011;Ramalhinho et al, 2011;Aguiar et al, 2012;Ramalhinho et al, 2012;Saxena et al, 2013;Khabaz, 2014;Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies revealed GSTP1 polymorphism has no correlation with clinical and pathologic tumor characteristics (Buser et al, 1997;Huang et al, 2003) only a few studies showed an inverse correlation with ER (Gilbert et al, 1993;Silvestrini et al, 1997;Moureau-Zabotto et al, 2006). Furthermore, two studies of Pongtheerat and colleagues reported that GSTP1 polymorphism was unrelated to increased risk of breast cancer, but found an inverse relationship between GSTP1 genotype and progesterone receptor protein (Pongtheerat et al, 2009;Pongtheerat et al, 2011), and positive correlation with better tumor differentiation and grade (Cairns et al, 1992;Haas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation